IMPLEMENTASI GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KOMITMEN DAN PRODUKTIVITAS GURU - Daman Rasman Syarif Hidayat (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
In education, transformational leadership is a model of leadership that is used in classrooms. This is important since the principal serves as the school's boss. As founders, they are responsible for bringing their vision and purpose to life. The aim of this analysis is to ascertain the importance of transformational leadership in increasing teacher engagement and success as a motivating factor in education. This research employs a qualitative approach in conjunction with a literature review. The findings indicate that a principal's transformational leadership has the potential to transform an individual from the fundamental thoughts and behaviors that underpin their execution of their duties into an efficient leadership style that results in consistent performance and continues to increase.